Estimation of the main dimensions of the traction permanent magnet-assisted synchronous reluctance motor - B. G. Liubarskyi (National Technical University "Kharkiv Polytechnic Institute", 2021)
Goal. The goal of the research is to develop an algorithm for selecting the main dimensions of a traction permanent magnet-assisted synchronous reluctance motor. Methodology. A method for determining the main dimensions of the motor, which combines the analytical selection of stator parameters and numerical field calculations for the selection of rotor parameters. The need to check the mechanical strength of a rotor with permanent NdFeB magnets in flux barriers is shown. Results. The article proposes an algorithm for selecting the main dimensions of a traction permanent magnet-assisted synchronous reluctance motor, which combines analytical expressions for selecting stator parameters and numerical field calculations for selecting rotor parameters. It is determined that analytical methods for calculating the magnetic circuit need to be developed in order to reduce the time to select the main dimensions of the motor. Originality. For the first time the sizes of active parts of the permanent magnet-assisted synchronous reluctance motor with power of 180 kW for the drive of wheels of the trolleybus are defined. Practical significance. As a result of research the sizes of active parts, stator winding data and a design of a rotor of the electric motor are defined. The obtained results can be applied when creating an electric motor for a trolleybus.